2009
DOI: 10.1080/14647270903037751
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis for the prevention of sickle cell disease: Current trends and barriers to uptake in a London teaching hospital

Abstract: Although PGD for prevention of the birth of a child affected by SCD is a viable treatment option for couples at risk of having an affected child, potential barriers to uptake of this service need to be fully addressed to ensure its availability to all couples seeking to avoid having a child affected with SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…The present prospective cohort study from an inner‐city tertiary PGD referral centre in London showed that for couples at risk of having an offspring affected with SCD, the live‐birth rate for PGD per couple embarking on PGD treatment was 63% after a mean of 1·2 fresh PGD cycles started. These figures are significantly higher than previous reports over the last two decades, in which the live‐birth rate following PGD ranged between 13% and 53% 18–21 . Furthermore, recently published data from the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium 22 reported a clinical pregnancy rate of 31% per embryo transfer, compared to 55% clinical pregnancy rate per embryo transfer in our present study.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The present prospective cohort study from an inner‐city tertiary PGD referral centre in London showed that for couples at risk of having an offspring affected with SCD, the live‐birth rate for PGD per couple embarking on PGD treatment was 63% after a mean of 1·2 fresh PGD cycles started. These figures are significantly higher than previous reports over the last two decades, in which the live‐birth rate following PGD ranged between 13% and 53% 18–21 . Furthermore, recently published data from the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium 22 reported a clinical pregnancy rate of 31% per embryo transfer, compared to 55% clinical pregnancy rate per embryo transfer in our present study.…”
Section: Discussioncontrasting
confidence: 82%
“…These figures are significantly higher than previous reports over the last two decades, in which the live-birth rate following PGD ranged between 13% and 53%. [18][19][20][21] Furthermore, recently published data from the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium 22 reported a clinical pregnancy rate of 31% per embryo transfer, compared to 55% clinical pregnancy rate per embryo transfer in our present study. The embryo-implantation rate was also higher in our present study compared to the study of De Rycke et al 22 (50% vs. 23%).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Although hESCs have been generally useful in dissecting disease mechanisms (as demonstrated in Lesch-Nyhan-specific hESC lines, which successfully recapitulated the disease phenotype of increased uric acid production as a result of hypoxanthineguanine phosphoribosyltransferase (HPRT) mutations, allowing further insights into the disease mechanisms and enabling drug screening(16)), their use in ESC-based therapy has resulted in moral and ethical issues associated with the requisite blastocyst destruction. In addition, clinical studies with hESCs are limiting as PGD is restricted to the diagnosis of embryos coming from a limited group of genetic disorders such as Fragile X syndrome (17), cystic fibrosis (18), and sickle cell disease (19).…”
Section: Cellular Reprogrammingmentioning
confidence: 99%